DISCOVERY LEARNING DAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SEKOLAH DASAR - Azmy, Bahauddin; Yustitia, Via (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
is research is motivated by the low learning outcomes of mathematics in Indonesia, as evidenced by the results of the Trend International Mathematics and Science Study (TIMMS) which states that the level of critical thinking ability of students in Indonesia is very low. PISA data shows that Indonesia is ranked 50th out of 57 countries with an average score of 391. The purpose of this study was to determine whether or not the discovery learning model had an effect on students' critical thinking skills on the volume block material for class V SDN Kebondalem Mojosari. The type of experimental research in this study was a posttest-only with Noneequivalent design. The population is all fifth grade students of SDN Kebondalem Mojosari. The technique in this study uses cluster random sampling. The sample used in this study used class VA and VB students at SDN Kebondalem Mojosari. This research method is a test. The instrument in this study used a critical thinking ability test sheet. Data analysis used was homogeneity test, normality test and T test. The results showed that there was an effect of the Discovery Learning model on students' critical thinking skills on the volume block material for class V SDN Kebondalem Mojosari. This is evidenced by the average critical thinking ability of the experimental class is better than the control class